Impact of Telehealth on Chronic Disease Control: A Narrative Review - Wróbel, Szymon; Wiązania, Kamil Andrzej; Wilczyński, Rafał; Wrona, Weronika; Dorożalska, Małgorzata; Owsik, Julia; Wdowiak, Wiktoria; Ludwisiak, Hanna (Quality in Sport, 2026)
Background. With the continuous development of new technologies, especially digital technologies, the possibilities provided by telehealth continue to increase. Research shows that the use of telehealth tools can be successfully used for managing patients with chronic conditions. Aim. As the number of chronic conditions within the world’s population rises, their effect becomes evident in terms of lowering patients’ quality of life and life expectancy. Telehealth can be an effective solution to this growing problem. This review is intended to examine the state-of-the-art studies in relation to the effect of telehealth on chronic disorder management, focusing mainly on clinical outcomes, quality of life, and healthcare costs. Material and methods. We reviewed the available scientific literature in databases such as PubMed, Scopus, and Web of Science. We included original research studies, systematic reviews, and meta-analyses that examined the impact of telehealth technologies on the management of patients with chronic diseases and were published in Polish or English between January 2020 and May 2026. Results. From the cited literature, it is clear that the use of telehealth has shown effectiveness in managing chronic disease. Although positive results can be observed in the short-term control of diseases such as hypertension, heart failure, diabetes, asthma, and chronic obstructive pulmonary disease, the effects of long-term management are unknown. Conclusions. This narrative review provides important insights regarding both the possible benefits and constraints of telehealth when managing chronic diseases. With the increasing use of telemedicine, it is vital to consider such difficulties and make sure that telehealth is accessible and efficient for all chronic patients.